An integrated framework for anticipating the future and dealing with uncertainty in policymaking. (December 2020) - van Dorsser, Cornelis; Taneja, Poonam; Walker, Warren; Marchau, Vincent
Highlights: The link between anticipatory Futures work and Policymaking is only moderate. A stronger link between Policymaking and Futures is possible via Policy Analysis. Policy Analysis and Policymaking are closely linked through an uncertainty typology. Futures and Policy Analysis can be linked through the uncertainty typology. This creates an Integrated Framework for Futures, Policy Analysis, and Policymaking. Abstract: Policymakers need to make policies for an uncertain future, and policy analysts assist policymakers in choosing preferred courses of action. Despite a longstanding recognition that the futures field can contribute a great deal to policy analysis, futures work is not used to its full potential as an element of policy analysis. This is partly due to an absence of well-defined links between the fields and a common unambiguous typology. This paper proposes a framework for linking policy analysis, policymaking, and the futures field so that they can benefit mutually from a shared approach and tools. This integrated framework is intended to guide policy analysts on the appropriate use of futures approaches so that they can improve their analyses and contribute to better policies. At the same time, futures practitioners will be encouraged to align their approaches with the needs of policy analysts, thereby leading to increased uptake of futures work in policy analysis.